PAM-8 IM/DD Transmission Based on Modified Lookup Table Nonlinear Predistortion - Jiao Zhang; Pengqi Gou; Miao Kong; Kaibo Fang; Jiangnan Xiao; Qi Zhang; Xiangjun Xin; Jianjun Yu (IEEE Photonics Journal, 2018)
In this paper, a modified lookup table (LUT) nonlinear predistortion method is proposed. With the modified LUT method, the number of patterns and the computational complexity can be reduced by half with a similar system performance comparing with normal LUT. We experimentally demonstrate an 8-ary pulse amplitude modulation (PAM-8) intensity modulation and direct detection (IM/DD) transmission over 15-km fiber using a directly modulated laser (DML) based on modified LUT. Around 1-dB receiver sensitivity improvement at bit-error ratio of 3.8 × 10 –3 is achieved by adopting a modified LUT over 15-km fiber transmission at 2 Gbaud based on a commercial DML. In addition, we also experimentally demonstrate Mach–Zehnder modulator based 40 Gbaud PAM-8 IM/DD transmission under back-to-back case, about 1-dB receiver sensitivity can also be improved.